A study of V(D)J recombination and DNA-damage response factors - Mensch, Kyna (University of Ottawa (Canada), 2008)
DNA double-stranded breaks (DSBs) represent a significant threat to genomic integrity, as failure to repair, or the incorrect repair of these lesions can lead to tumour formation and carcinogenesis. These breaks are not only caused by external factors, but are also generated within cells during regulated physiological processes, such as V(D)J recombination. This process is essential for lymphocyte development and involves the activity of factors involved in the non-homologous end-joining (NHEJ) repair pathway. A tri-partite study of V(D)J recombination and DNA damage response factors was conducted in order to gain insight into these overlapping pathways. The factors examined include Rag-1 (a component of the recombinase complex that initiates V(D)J recombination); Ku70 (a subunit of the Ku heterodimer involved in NHEJ and V(D)J recombination); Artemis (a nuclease involved in NHEJ and V(D)J recombination); and the Octamer-binding transcription factor-1 (which contributes to cellular survival post-DNA damage). The three facets of this study include (i) defining the Ku70 binding region of Rag-1 through the use of association assays, (ii) examining the regulation of ectopic Artemis expression in non-permissive cells, and (iii) identifying Oct-1 interacting factors with the use tandem affinity purification.
Keywords: Chemistry, Biochemistry.